VisFlow: A Relational Platform for Efficient Large-Scale Video Analytics - Lu, Yao; Chowdhery, Aakanksha; Kandula, Srikanth (Microsoft, 2016)
We describe VisFlow, a system that efficiently analyzes the feeds from many cameras. Ubiquitous camera deployments are widely used for security, traffic monitoring, and customer analytics. However, existing methods to analyze the video feeds in real-time or post-facto do not scale and are error-prone. Our key contributions are two-fold. Surveillance video is hard to analyze because it has low-resolution, many objects per frame, varying light, etc. By leveraging the fixed perspective of surveillance cameras, we show that typical vision tasks can be performed with high accuracy. Next, to efficiently process many feeds, we use a relational dataflow system. We observe that (i) even vision queries that seem different have common parts (e.g., background subtraction and feature extraction), (ii) often neither camera-level or frame-level parallelism lead to good executions, and (iii) the best execution plans vary with input size. By extending query optimization techniques, VisFlow computes efficient execution plans for vision queries, parallelizing as needed. Evaluation on traffic videos from a large city on complex vision queries shows many fold improvements in accuracy, query completion time and resource usage relative to existing systems.